Transient photoconductivity and free carrier dynamics in a monolayer WS2 probed by time resolved Terahertz spectroscopy. (15th April 2019) - Xu, Shujuan; Yang, Jin; Jiang, Huachao; Su, Fuhai; Zeng, Zhi
Abstract: The frequency and time resolved conductivity in a photoexcited large-area monolayer tungsten disulfide (WS2 ) have been simultaneously determined by using time-resolved terahertz spectroscopy. We use the Drude–Smith model to successfully reproduce the transient photoconductivity spectra, which demonstrate that localized free carriers, not bounded excitons, are responsible for the THz transport. Upon the optical excitation with 400 nm and 530 nm wavelength, the relaxation dynamics of the free carriers include fast and slow decay components with time constants approximately smaller than 1 ps and between 5–7 ps, respectively. The former sub-picosecond decay is attributed to the charge carrier loss induced by the exciton formation, while both the Auger recombination and the surface trapping can contribute to the slow relaxation.